Arduino performance in control systems for converting air-to-water - Triwahyudin Rohman; Naufal Waliy Ishlah; Salvatore Johanes Rega; Subekti Subekti (JTTM : Jurnal Terapan Teknik Mesin, 2024)
Humans are unable to function without water. Water is therefore necessary for living. This study will address the advantages of converting air into drinkable water based on this premise. Regarding the condensation process itself, it is not the best option to use it in remote locations because it needs a lot of energy and equipment. Consequently, thermoelectric technology was used in this study to replace the condensation process. This tool's easier thermoelectric operation makes it suitable for usage in remote locations. The design of an effective Arduino program control system should take into account the effects of temperature and humidity condition parameters on the environment to maximize water production. This will allow the performance between supporting sensors and the main components to be automatically optimized under a variety of environmental conditions and produce water without wasting excessive energy. As a result, the trial where the average temperature was 30°C and the average humidity was 81% produced the highest results for the researchers when they calculated the environmental condition factors that were already known. Within the hour-long study session, 6 milliliters of water were created. In addition to the efficiency with which the Arduino program is commanded, from all sensors to the primary thermoelectric components, it can execute commands automatically and optimally. It can also resolve issues that affect the air-to-water converter controller's performance in a way that ensures proper operation of all controllers by taking into account the relevant factors. to the fullest without squandering too much energy